EXPRESSING OPINIONS AND GIVING REASONS AS A STRATEGY TO INCREASE THE STUDENTS’ SPEAKING PERFORMANCE. FOR SECOND GRADE (A Collaborative Action Research at Al-Zahrah Islamic Boarding School) - Lara Azlia; Misnawati (Journal of English Education and Social Science, 2021)
The research of using Expressing Opinions (EO) and Giving Reasons (GR) as a strategy to increase the students’ speaking performance has been done at Al-Zahrah Islamic Boarding School. It was begun from July 13 2020 until August 8 2020. The problems of this research are; how does EO and GR increase the students’ speaking performance in second grade at Al-Zahrah? And how do the students respond toward the implementation of EO and GR as a strategy? Based on the research problems, there are two purposes of the research, namely; to know EO and GR increase the students’ speaking performance and to know the students respond toward in speaking after practicing EO and GR as a strategy. The scope of this research focus on the strategy EO and GR and activities that will improve students’ skill at Al-Zahrah Islamic Boarding School. In this research, the researcher focused on expressing opinions and giving reasons. The design of this research was a collaborative action research. It was design to improve the students’ skill to enhance their skill in speaking through EO and GR (Expressing Opinions and Giving Reasons) a strategy to increase the students’ speaking performance. The results of the research using Expressing Opinions (EO) and Giving Reasons (GR) as a strategy to increase the students’ speaking performance showed that the class average score in cycle 2 increased to 77.06, from the result of post-test in cycle 1 which was 67.05. The analysis of the increase in students’ learning activeness was obtained through the results of observing students’ activity during the learning process that collected from the observation sheet which results showed a significant increase in student activeness. Based on the research results, it can be concluded that the implementation of Expressing Opinions (EO) and Giving Reasons (GR) as a strategy can improve the speaking performance of 2nd grade students of Al-Zahrah Islamic Boarding School.